2020
DOI: 10.1093/nar/gkaa615
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of BCL-2 by acridone derivative through gene promoter i-motif for alleviating liver damage of NAFLD/NASH

Abstract: Nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH) are global epidemic public health problems with pathogenesis incompletely understood. Hepatocyte excessive apoptosis is a significant symbol for NAFLD/NASH patients, and therefore anti-apoptosis therapy could be used for NAFLD/NASH treatment. Up-regulation of BCL-2 has been found to be closely related with anti-apoptosis. BCL-2 gene promoter region has a C-rich sequence, which can form i-motif structure and play important role in regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Apoptosis can be regulated by mitochondrial-mediated endogenous pathway [ 78 ]. Bcl-2 and Bax both belong to the Bcl-2 family; Bcl-2 belongs to anti-apoptotic gene, and Bax belongs to pro-apoptotic gene [ 79 ]. Both of them play an essential role in regulating the process of apoptosis through mitochondrial pathway [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis can be regulated by mitochondrial-mediated endogenous pathway [ 78 ]. Bcl-2 and Bax both belong to the Bcl-2 family; Bcl-2 belongs to anti-apoptotic gene, and Bax belongs to pro-apoptotic gene [ 79 ]. Both of them play an essential role in regulating the process of apoptosis through mitochondrial pathway [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies establishing the i-motif within the BCL2 promoter as a transcriptional activator [46,47] support the premise that stabilization of the BCL2 i-motif in NAFLD and NASH is an effective approach to increase BCL2 levels and prevent hepatocyte apoptosis. Ding Li's laboratory identified an acridone derivative, A22, as a high-affinity stabilizer of the BCL2 i-motif ( Figure 3) [143]. In order to demonstrate preferential selectivity, they tested the compound against the BCL2 G4, duplex DNA, and several other i-motif sequences.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Moreover, treatment of hepatocytes, grown in palmitic acid oil to mimic the lipid-induced apoptotic environment of NASH, with A22 resulted in a robust increase in cell viability and a decrease in activation of the apoptotic cell death pathway. Since NAFLD and NASH are tightly linked to metabolic syndrome, the authors also examined the effect of A22 treatment on glucose uptake and demonstrated that A22 was significantly more efficacious in stimulating the influx of glucose into hepatocytes compared to the metformin, the frequently prescribed treatment for insulin resistance [143]. Compound A22 also performed well in a NAFLD/NASH mouse model where treatment led to elevated BCL2 levels, less apoptosis, and decreased markers of hepatocyte injury and metabolic syndrome (e.g., weight gain not associated with food intake, insulin resistance, and elevated serum cholesterol and triglycerides).…”
Section: Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL-2 proteins can contribute to hepatic ROS formation, in addition ROS levels can trigger cell death through BCL-2 protein modulation. The antiapoptotic BCL-2 protein is diminished in NAFLD/NASH and its overexpression can reduce hepatic apoptosis [72]. BCL-2 proteins regulate ROS/oxidative stress-mediated apoptosis, but can conversely be regulated by ROS signaling via phosphorylation and ubiquitination [73].…”
Section: Ros-mediated Regulation Of Bcl-2 Proteinsmentioning
confidence: 99%